Assessing the health, safety, and environment culture in the United Arab Emirates oil and gas industry. Issue 2 (3rd October 2019) - Almazrouei, Mohmaed; Khalid, Khalizani; Abdallah, Salam; Davidson, Ross
Abstract : Purpose: This paper aims to assess the ways through which the concept of health, safety and environment (HSE) is perceived by workers in the United Arab Emirates (UAE) oil and gas industry. The study focused on different aspects of the HSE culture and how employees with and without leadership responsibilities differed in their conceptualization of HSE culture. Design/methodology/approach: Semi-structured interviews were conducted for 30 staff of the state-owned Abu Dhabi National Oil Company in the UAE. The interviewees were purposively selected which included both those in leadership and non-leadership roles. Findings: The findings revealed that the interviewees viewed HSE culture as a descriptive term, a causal phenomenon, a systemic approach or a legal requirement/obligation. Interviewees in the production and maintenance units mentioned safety most often. Employees and managers exhibited negligible differences in their usage of the HSE culture concept. Managers predominantly featured in the narratives as important drivers of HSE culture. Physical conditions, behavior and procedures, management, competence and collaboration emerged as important components of a sound HSE culture. Originality/value: To enable better communication and subsequent improvement of the HSE culture, an analogical HSE culture "vehicle" was developed in the study. The vehicle is a novel illustration based on the key roles of managers and employees, as well as the main components of a sound HSE culture.